The original coordination chemistry of 2-phosphaphenol with copper(I) and gold(I) halides - Mao, Yanli (2013)
2-Phosphaphenol (L) forms unusual complexes with copper and gold halides. With CuCl, a dimeric [L2CuCl]2 complex is observed with L acting both as η1-P terminal and μ2-P bridging ligand and a copper–copper short contact of 2.549 Å. With copper bromide, a distorted infinite chain [L2CuBr]n is formed, whereas with copper iodide, the zigzag chain [L2CuI]n is observed. The phosphaphenol acts as a terminal ligand coating the CuX molecular wires. With gold chloride, a dimeric [LAuCl]2 complex is formed, which is held by an aurophilic interaction at 3.132 Å.